The effects of an HIV project on HIV and non-HIV services at local government clinics in urban Kampala - Kyegombe Nambusi; Etonu Allan; Manabe Yukari C; Matsubayashi Toru; Muganzi Alex; Coutinho Alex; Peters David H (BMC, 2011)
Abstract Background HIV/AIDS is a major public health concern in Uganda. There is widespread consensus that weak health systems hamper the effective provision of HIV/AIDS services. In recent years, the ways in which HIV/AIDS-focused programs interact with the delivery of other health services is often discussed, but the evidence as to whether HIV/AIDS programs strengthen or distort overall health services is limited. The aim of this study was to examine the effect of a PEPFAR-funded HIV/AIDS program on six government-run general clinics in Kampala. Methods Longitudinal information on the delivery of health services was collected at each clinic. Monthly changes in the volume of HIV and non-HIV services were analyzed by using multilevel models to examine the effect of an HIV/AIDS program on health service delivery. We also conducted a cross-sectional survey utilizing patient exit interviews to compare perceptions of the experiences of patients receiving HIV care and those receiving non-HIV care. Results All HIV service indicators showed a positive change after the HIV program began. In particular, the number of HIV lab tests (10.58, 95% Confidence Interval (C.I.): 5.92, 15.23) and the number of pregnant women diagnosed with HIV tests (0.52, 95%C.I.: 0.15, 0.90) increased significantly after the introduction of the project. For non-HIV/AIDS health services, TB lab tests (1.19, 95%C.I.: 0.25, 2.14) and diagnoses (0.34, 95%C.I.: 0.05, 0.64) increased significantly. Noticeable increases in trends were identified in pediatric care, including immunization (52.43, 95%C.I.: 32.42, 74.43), malaria lab tests (1.21, 95%C.I.: 0.67, 1.75), malaria diagnoses (7.10, 95%C.I.: 0.73, 13.46), and skin disease diagnoses (4.92, 95%C.I.: 2.19, 7.65). Patients' overall impressions were positive in both the HIV and non-HIV groups, with more than 90% responding favorably about their experiences. Conclusions This study shows that when a collaboration is established to strengthen existing health systems, in addition to providing HIV/AIDS services in a setting in which other primary health care is being delivered, there are positive effects not only on HIV/AIDS services, but also on many other essential services. There was no evidence that the HIV program had any deleterious effects on health services offered at the clinics studied.